Bacteriophage Administration Reduces the Concentration of Listeria monocytogenes in the Gastrointestinal Tract and Its Translocation to Spleen and Liver in Experimentally Infected Mice. (24th June 2010) - Mai, Volker; Ukhanova, Maria; Visone, Lee; Abuladze, Tamar; Sulakvelidze, Alexander
Abstract : To investigate the efficacy of phage supplementation in reducing pathogen numbers, mice were treated via oral gavage with a Listeria monocytogenes phage preparation (designated ListShield) before being orally infected with L. monocytogenes . The concentrations of L. monocytogenes in the liver, spleen, and intestines were significantly lower (P < . 05 ) in the phage-treated than in the control mice. Phage and antibiotic treatments were similarly effective in reducing the levels of L. monocytogenes in the internal organs of the infected mice. However, the significant weight loss detected in the control and antibiotic-treated groups was not observed in the infected, ListShield-treated mice. Long-term (90 days), biweekly treatment of uninfected mice with ListShield did not elicit detectable changes in the microbiota of their large intestines or deleterious changes in their health. Our data support the potential feasibility of using bacteriophages to control proliferation of L. monocytogenes in mice without affecting commensal microbiota composition.